Istinbath Hukum Islam Masa Kenabian dan Sahabat: Sejarah, Karakteristik, dan Metode Ijtihad dalam Membentuk Hukum Islam - Rizani, Rasyid; Jalaluddin, Jalaluddin; Azhari, Fathurrahman; Hamdi, Fahmi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This paper discusses the history, characteristics, and methods of istinbath of Islamic law during the prophetic and Companion periods. It explains how Islamic law developed along with the revelation to the Prophet Muhammad and how the Companions used ijtihad in determining the law. It also discusses the differences of opinion among the Companions and how they struggled to resolve legal issues using the original sources of Islamic law, the Qur'an and Sunnah. The Prophetic period, known as the infancy period, is the period of growth and formation of the Prophet's Islamic law for 23 years, from his elevation to the Apostleship in 610 AD until his death in 632 AD. This period is divided into two parts, namely the Mecca period and the Medina period. The characteristics of Islamic law during the prophetic period include several important aspects, such as tashri' divided into two phases with different focuses. The determination of law during the prophetic period began with events or questions posed by the people of Muhammad Saw to him. Meanwhile, the Companion period is also called the development period, and the characteristic of tashri' in this period is that ijtihad has begun to be carried out by the Companions because the Prophet as the authority of tashri' has passed away. Keywords: History, characteristics, istinbath method, Islamic Law Abstrak Tulisan ini membahas tentang sejarah, karakteristik, dan metode istinbath hukum Islam masa kenabian dan sahabat. Ia menjelaskan bagaimana hukum Islam berkembang seiring dengan turunnya wahyu kepada Nabi Muhammad saw dan bagaimana para sahabat menggunakan ijtihad dalam menetapkan hukum. Tulisan ini juga membahas tentang perbedaan pendapat di antara para sahabat dan bagaimana mereka berjuang untuk menyelesaikan masalah hukum dengan menggunakan sumber asli hukum Islam, yaitu Al-Qur'an dan Sunnah. Pada Periode kenabian, dikenal sebagai masa pertumbuhan, adalah masa pertumbuhan dan pembentukan hukum Islam Rasulullah selama 23 tahun, dari diangkatnya menjadi Rasul pada tahun 610 M hingga wafatnya pada tahun 632 M. Periode ini dibagi menjadi dua bagian, yaitu periode Mekkah dan periode Madinah. Karakteristik hukum Islam pada masa kenabian mencakup beberapa aspek penting, seperti tasyri' dibagi menjadi dua fase dengan fokus yang berbeda. Penetapan hukum di masa kenabian dimulai dengan peristiwa atau pertanyaan yang diajukan oleh umat Muhammad Saw kepadanya. Sedangkan, Periode sahabat disebut juga masa perkembangan, dan ciri khas tasyri’ pada periode ini adalah ijtihad sudah mulai banyak dilakukan oleh para sahabat karena Rasulullah saw sebagai pemegang wewenang tasyri’ sudah meninggal dunia. Kata kunci: Sejarah, karakteristik, metode istinbath, Hukum Islam